Mainland Chinese Students’ Attitudes to Hong Kong English - Shengnan, Li; Ting, Su Hie (Journal of Linguistics and Communication Studies, 2022)
This study investigates the overt and covert attitudes of China Mainland undergraduate students towards Hong Kong English(HKE)through questionnaires and verbal-guise technique(VGT).The questionnaire showed the participants’ negative attitude towards Hong Kong English, and the female participants showed a more inclusive attitude than the males. For VGT, participants rated two recordings of HKE speech on a bipolar semantic scale with 16 adjectives. The results showed that the male HKE speaker was evaluated more highly than the female speaker on both status and solidarity. The female and male participants were significantly different in their ratings of the three status traits (confidence, hardworking and fluency), with female participants being stricter. The study suggests the aspects of language attitudes in which there are disparities need to be further explored using direct and indirect measures.